BOMBYX MORI SILK FIBER–REINFORCED COMPOSITE STRIP CROWN FOR EARLY CHILDHOOD CARIES: A CASE REPORT - Endytiastuti, Endytiastuti; Wardani Mahendra, Putri Kusuma (FKG ULM, 2026)
Background: Early childhood caries (ECC) commonly affects multiple teeth and can rapidly progress to pulpal necrosis. Managing and maintaining affected teeth until their natural exfoliation presents a clinical challenge. A promising conservative approach involves the use of strip crowns reinforced with Bombyx morisilk fiber–reinforced composite following endodontic therapy. Objective: This case report describes the restoration of primary maxillary incisors with severe crown destruction due to ECC using Bombyx mori silk fiber–reinforced composite posts and strip crowns after root canal treatment. Case: A 5-year-8-month-old boy presented to the Pediatric Dentistry Clinic, Prof. Soedomo Dental Hospital, Universitas Gadjah Mada, accompanied by his mother, with a complaint of several decayed upper anterior teeth. The child had a history of nocturnal breastfeeding and daily UHT milk consumption, along with poor oral hygiene. Clinical examination revealed dentinal caries on teeth 51, 52, and 62, and severe crown destruction with pulpal necrosis on tooth 61. Managing case: Root canal treatment was performed on tooth 61, followed by placement of a Bombyx mori silk fiber–reinforced composite post and strip crown restoration. Strip crown restorations were also placed on teeth 51, 52, and 62. At the one-month follow-up, all restorations remained intact, functional, and aesthetically pleasing, with no dislodgement or failure observed. Conclusion: Strip crowns represent an effective and aesthetic restorative option for children with ECC, particularly in the anterior region. The use of Bombyx mori silk fiber–reinforced composite posts in cases of severe coronal destruction enhances retention, durability, and long-term clinical outcomes.Keywords:Bombyx Mori Silk Fiber Reinforced Composite, Early Childhood Caries, Strip Crown